Pengembangan E-Modul berbasis Flipbook menggunakan Model Pengembangan Addie pada Siswa Kelas XI Mata Pelajaran Desain Grafis Percetakan di SMKN 02 Singosari - Faradilla Umami; Satrio Hadi Wijoyo; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
In the time of pandemic almost all the school to carry out learning activities from the house, so that the media is able to help the students to learn from home. on the subjects of Graphic Design Printing during the pandemic using the media of learning-shaped power point. E-module is very helpful if dikembangkanPenelitian this begins with the stage of analysis of learning, then the design of learning media with design wireframe, and then perform a stage of development with the preparation of the material using Microsoft word and the design of the e-module using corel-draw, after the design is so done export the file into a pdf, then export into a flipbook using a pdf flipbook professional, for the writer to know whether the media was already fairly well implemented, the authors use a questionnaire validation to media experts and material experts for assessment, dilanjutnkan with stage evaluation using pre-test and post-test that will be answered by the students. The results of the normality test for pre-test and post-test is a significance value of pre-test 0.006, post-test of 0.000 and a questionnaire of 0.000. Furthermore, the data entered into the test statistic non parametric with the formula Wilcoxon Test and get hadil 0,002. Based on these values, it can be concluded that the value of significance is less than 0.05, then the results of the Ha is accepted and Ho is rejected, with the writing of the hypothesis that â€œThere is an increase in learning outcomes of students after being given the media of learningâ€.